Optimation of avocado fruit added on the ice cream product of coconut milk - Wijana, Susinggih; Effendi, Usman; Setiati, Elis (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
Avocado fruit is perishable product, therefore to prolong a self live product have to processing applied. One of product a suitable to be done of avocado fruit is processing to ice cream, because this product had a high content of lipid as contain in avocado fruit. The avocado substitution on ice cream product, another as diversification product also to decrease the milk content which do not preferred by most of Indonesia people which have a characteristic of lactose intolerance. The aim of this study is to find out the best composition of ice cream made from substitution of avocado fruit, and then can be yielded the high quality of ice cream product. The result shows that addition of 20% avocado fruit can be improve the ice cream quality, by the moisture content of 36.77%, protein 1.60%, lipid 23.53%, thawing 62.62 minutes, taste value 5.35 (preferred), color 5.75 (preferred), aroma 5.65 (preferred) and texture value of 6.34 (very preferred). Â Keywords: avocado fruit, optimation, ice cream and coconut milk